The Self-Deceived Consumer: Women’s Emotional and Attitudinal Reactions to the Airbrushed Thin Ideal in the Absence Versus Presence of Disclaimers - Borau, Sylvie (Journal of business ethics, 2019)
The use of airbrushed “thin ideal” models in advertising creates major ethical challenges: This practice deceives consumers and can be harmful to their emotional state. To inform consumers they are being deceived and reduce these negative adverse effects, disclaimers can state that the images have been digitally altered and are unrealistic. However, recent research shows that such disclaimers have very limited impact on viewers. This surprising result needs further investigation to understand how women who detect that images have been airbrushed are still harmed by them. Three studies reported in this article address this question. The authors identify a typology, based on a combination of three emotional reactions experienced by women who are exposed to the airbrushed thin ideal. In further analyses, they investigate how detection of airbrushing—whether spontaneous or with the help of a disclaimer—relates to these emotional reactions and women’s attitudes to altered images. Results show that detection of airbrushing does not systematically protect women from either wanting to look like airbrushed thin models or the negative emotions triggered by exposure to thin ideal images, nor does it always generate defensive reactions toward ads using such images. Women who detect that images have been airbrushed may still process these images as realistic. In addition to discussing this irrational process of self-deception, this article suggests policy interventions to prevent it.